La lógica de Stalin y la Guerra de España - Antonio Elorza (Cahiers de Civilisation Espagnole Contemporaine)
Beyond its repressive dimension, Stalin is able to define his own way of dealing with politics, through a personal approach to the resolution of conflicts born from the war of classes, at the same time implacable and pragmatic. The civil war in Spain becomes an optimal scenario for the application of this strategy.